Frequency of major avalanche winters - Fitzharris, B. B.; Schaerer, P. A. (Journal of Glaciology, 1980)
A 70-year record has been compiled for avalanches affecting the Canadian Pacific Railway at Rogers Pass, British Columbia. Time series are presented for avalanche frequency, avalanche mass, and length of avalanche debris on the rail line for 26 avalanche paths as well as for winter snow-fall. Winters with the heaviest avalanche activity were 1971-72, 1934-35, 1919-20, 1932-33, and 1953-54. Time- series analysis indicates that the size of avalanches has decreased in recent decades. Spectral analysis shows avalanche activity to be similar to white noise but with a weak periodicity of about 18 years. An examination of the climatology of big avalanche winters reveals two distinct circulation patterns: a strong zonal flow with frequent Pacific storms and heavy snow-fall; or a pronounced meridional flow, Arctic air outbreaks, and catastrophic avalanching released by rapid advection of warm moist Pacific air. Major avalanche winters need not be big snow- fall winters. Les auteurs ont compilé des données recueillies depuis 70 ans concernant les avalanches ayant eu un effet sur la voie ferrée du Canadien Pacifique au col de Rogers en Colombie- Britannique. Ils présentent des séries chronologiques pour la fréquence des avalanches, la masse des avalanches, la longueur de débris laissés par l'avalanche sur la voie ferré e pour 26 couloirs d'avalanche et les précipitations de neige en hiver. L'activité des avalanches a été la plus considérable au cours des hivers 1971-72, 1934-35, 1919-20, 1932-33 et 1953-54. L'analyse des séries chronologiques indique que la taille des avalanches a diminué au cours des dernières décennies. L'analyse spectrale montre que l'activité des avalanches est similaire au bruit blanc, mais avec une faible périodicité d'environ 18 ans. Une étude de la climatologie des années propices aux fortes avalanches montre deux schémas de circulation: une forte circulation zonale avec de fréquentes tempêtes en provenance du Pacifique et des chutes de neige abondantes; ou une circulation méridionale prononcée, ...